Burkholderia cepacia Complex Species Differ in the Frequency of Variation of the Lipopolysaccharide O-Antigen Expression During Cystic Fibrosis Chronic Respiratory Infection - Hassan, A. Amir; Coutinho, Carla P.; Sá-Correia, Isabel (Frontiers in Cellular and Infection Microbiology, 2019)
Burkholderia cepacia complex (Bcc) bacteria can adapt to the lung environment of cystic fibrosis (CF) patients resulting in the emergence of a very difficult to eradicate heterogeneous population leading to chronic infections associated with rapid lung function loss and increased mortality. Among the important phenotypic modifications is the variation of the lipopolysaccharide (LPS) structure at level of the O-antigen (OAg) presence, influencing adherence, colonization and the ability to evade the host defense mechanisms. The present study was performed to understand whether the loss of OAg expression during CF infection can be considered a general phenomenon in different Bcc species favoring its chronicity. In fact, it is still not clear why different Bcc species/strains differ in their ability to persist in the CF lung and pathogenic potential. The systematic two-decade-retrospective-longitudinal-screening conducted covered 357 isolates retrieved from 19 chronically infected patients receiving care at a central hospital in Lisbon. The study involved 21 Bcc strains of six/seven Bcc species/lineages, frequently or rarely isolated from CF patients worldwide. Different strains/clonal variants obtained during infection gave rise to characteristic OAg-banding patterns. The two most prevalent and feared species, B. cenocepacia and B multivorans, showed a tendency to lose the OAg along chronic infection. B. cenocepacia recA lineage IIIA strains known to lead to particularly destructive infections exhibit the most frequent OAg loss, compared with lineage IIIB. The switch frequency increased with the duration of infection and the level of lung function deterioration. For the first time, it is shown that the rarely found B. cepacia and B. contaminans, whose representation in the cohort of patients examined is abnormally high, keep the OAg even during 10- or 15-year infections. Data from co-infections with different Bcc species reinforced these conclusions. Concerning the two other rarely found species examined, B. stabilis exhibited a stable OAg expression phenotype over the infection period while for the single clone of the more distantly related B. dolosa species, the OAg-chain was absent from the beginning of the 5.5-year infection until the patient dead. This work reinforces the relevance attributed to the OAg-expression switch suggesting marked differences in the various Bcc species.